PENEGAKAN HUKUM TERHADAP PELAKU PENYALAHGUNAAN PENGANGKUTAN BAHAN BAKAR MINYAK BERSUBSIDI - Prakasa, Surya; Fahmi, Sudi; Ardiansah, (The Juris, 2024)
In the explanation of Article 55, it is stated that abuse refers to activities aimed at gaining individual or corporate profits in a manner that harms the interests of the public and the state, such as through fuel adulteration, misallocation of subsidized fuel, and transportation and sale of subsidized fuel abroad. The purpose of this research is to analyze Law Enforcement Against Abuses in the Transportation of Subsidized Fuel Oil Offenders in Rokan Hilir based on Law Number 22 of 2001 concerning Oil and Natural Gas, and to analyze the obstacles and efforts to overcome obstacles in law enforcement against offenders in the transportation of subsidized fuel oil in Rokan Hilir based on Law Number 22 of 2001 concerning Oil and Natural Gas. The method used is socio-legal research. Based on the research results, it is found that law enforcement against offenders in the transportation of subsidized fuel oil in Rokan Hilir based on Law Number 22 of 2001 concerning Oil and Natural Gas has not been fully effective, as there are still traders who transport subsidized fuel oil by modifying vehicles or using jerry cans at every gas station in the Rokan Hilir region. Obstacles in law enforcement against offenders in the transportation of subsidized fuel oil in Rokan Hilir based on Law Number 22 of 2001 concerning Oil and Natural Gas include lack of coordination among relevant agencies, weak supervision over the misuse of subsidized fuel oil transportation, difficulty in gathering sufficient evidence, lack of public understanding regarding the misuse of subsidized fuel oil transportation in Rokan Hilir, and the need to evaluate and strengthen existing regulations. Implementing a more open reporting system and active participation in oversight programs by authorities are necessary to support more effective law enforcement.